EMPOWERMENT EDUCATION, PEER SUPPORT TERHADAP PERILAKU PENCEGAHAN CACAT DI RS KUSTA SUMBERGLAGAH - Arif, Taufan; Haryanto, Joni; Yunitasari, Esty (Unusa Press, 2017)
Leprosy disease is caused by Mycobacterium leprae which attacks the skin and peripheral nerves. Currently leprosy still remains a world problem. Leprosy patients should not experience severe structural and functional damage. The combination of the empowerment education, peer support can improve symptoms and signs of impairment, behavioral prevention defects. The objective of this study was describes empowerment education, peer support to behavior prevention of dissability. This study used true experimental randomized pre-post test control group design. The sampel was recruited using simple random sampling consisting of 16 respondents. The independent variable are empowerment education, peer support. The dependent variable are knowledge of disability prevention, attitude of disaility prevention, action of medication compliance. The data were collected by distributing questionnaires and check card patient treatment. Data were analized by Mann-Whitney Test and Wilcoxon Signed ranked Test. The result showed that 1) There is influence on knowledge, 2) There is influence on attitude , 3) There is influence on medication adherence. Supportive interventions through empowerment education, peer support can help leprosy patients in the treatment process. Proven knowledge, attitude, adherence to medication, and self efficacy intervention group increased after given intervention. Suggestions for further research is to examine the development of leprosy impairment prevention models based on other nursing theories and with a longer duration of study.